The Effects of Mung Bean Peptide and Its’ Complexes on the Treatment of Lead Poisoning - Wei Wei; Shue Wang; Xue-Jun Zhang; Jiu-Xun Zhang; Zheng-Wang Chen; Jia-Ying Huang; Ye-Wang Zhang (Journal of Food Quality)
Objective. To investigate the effects of mung bean peptide and its’ complexes on promoting lead excretion and neuroprotection of zebrafish. Methods. The lead poisoning models of zebrafish were established by lead acetate solution; the models were treated with high and low concentrations (58.3 and 175 μg/mL) of mung bean peptides, with high, medium, and low concentrations (27.8, 83.3, and 250 μg/mL) of mung bean peptide complexes, separately. The effects of the mung bean peptide complexes on the lead content, axonal fluorescence intensity, and peripheral motor nerve length changes were identified in the zebrafish model, and the effects of mung bean peptide and its’ complexes on zebrafish's lead excretion, axonal protection rate, and peripheral movement promotion rate of nerve regeneration were calculated. Results. The effects of high concentration of mung bean peptide (175 μg/mL) in promoting lead excretion was 29% (p<0.05), and the effect of high concentration of mung bean peptide complexes (250 μg/mL) in promoting lead excretion was 30% (p<0.05). The other concentrations of mung bean peptide and its’ complex groups did not show a noticeable lead excretion effect. The protective effects of mung bean peptide at concentrations of 58.3 and 175 μg/mL against zebrafish axonal injury were 98% and 101% (p<0.01), and the peripheral nerve regeneration promotion effects were 29% (p>0.05) and 42% (p<0.05), respectively. The protective effects of mung bean peptide complexes at concentrations of 27.8, 83.3, and 250 μg/mL against zebrafish axonal injury were 85%, 78%, and 93% (p<0.01); peripheral nerve regeneration promotion rates were 46%, 50%, and 50% (p<0.05). Conclusion. The mung bean peptide and its’ complexes can effectively promote the discharge of lead in the zebrafish lead poisoning and have protective and regeneration effects on zebrafish nerves.